Germline de novo mutations in families with Mendelian cancer syndromes caused by defects in DNA repair - Kitty Sherwood; Joseph C. Ward; Ignacio Soriano; Lynn Martin; Archie Campbell; Raheleh Rahbari; Ioannis Kafetzopoulos; Duncan Sproul; Andrew Green; Julian R. Sampson; Alan Donaldson; Kai-Ren Ong; et al. (Nature Communications, 2023)
Abstract DNA repair defects underlie many cancer syndromes. We tested whether de novo germline mutations (DNMs) are increased in families with germline defects in polymerase proofreading or base excision repair. A parent with a single germline POLE or POLD1 mutation, or biallelic MUTYH mutations, had 3-4 fold increased DNMs over sex-matched controls. POLE had the largest effect. The DNMs carried mutational signatures of the appropriate DNA repair deficiency. No DNM increase occurred in offspring of MUTYH heterozygous parents. Parental DNA repair defects caused about 20–150 DNMs per child, additional to the ~60 found in controls, but almost all extra DNMs occurred in non-coding regions. No increase in post-zygotic mutations was detected, excepting a child with bi-allelic MUTYH mutations who was excluded from the main analysis; she had received chemotherapy and may have undergone oligoclonal haematopoiesis. Inherited DNA repair defects associated with base pair-level mutations increase DNMs, but phenotypic consequences appear unlikely.